A review of the one registration system for contractors (1RoC) - Abdul Rashid, Khairuddin; Khairuddin, Samer Shahedza (Construction Research Institute of Malaysia, 2016)
This paper reports the outcome of a desk study on the Malaysian system for the registration of contractors in general and specifically on the newly introduced One Registration System for Contractors or 1RoC. Essentially, contractors are registered so as to ensure that only those with the acceptable level of resources, experience and expertise are permitted to carry out construction works. The evolution of the system can be said to comprise three phases. Initially it involved only contractors partaking in public sector works to be registered with a public agency known as Pusat Khidmat Kontraktor (PKK; Contractors Service Centre, CSC). The second phase was initiated with the passing of the CIDB Act 1994 which legally mandated registration of all contractors by the CIDB irrespective of whether they are participating in public or private sector works. Interestingly, a dual registration system was born. Then on 15th October 2012 the 1RoC (Sistem Satu Pendaftaran Kontraktor or SSPK) was introduced thereby completing the third phase. Key findings from the study include that the 1RoC in actual fact is not a new system rather a streamlined version of the CIDB's former registration system. Thus, with the 1RoC the previous PKK system is abolished, In addition, the 1RoC seems able to address critiques of the dual registration system whereby its implementation could lead to greater efficiencies. The implementation of the 1RoC is seen as a significant development in terms of the future development of the contracting services and the construction industry of Malaysia.